Low Mononuclear Cell IL-18 and IL-27 Response in Children: Susceptibility to Tuberculosis Infection after Contact - Karabacak, Hasan Azem; Yilmaz, Ozge; Tuglu, Ibrahim; Taneli, Fatma; Surucuoglu, Suheyla; Kanik, Esra Toprak; Ozkutuk, Nuri; Gozukara, Ceyhun; Ozkut, Mahmut Mustafa; Turkeli, Ahmet; Yuksel, Hasan (Journal of Pediatric Infectious Diseases, 2019)
Background Identification of the immune response against tuberculosis is vital to develop new diagnostic and therapeutic modalities. The objective of this study was to determine IL (interleukin)-18 and IL-27 responses of peripheral blood mononuclear cells to early secreted antigen (ESAT-6) and culture filtrate protein-10 (CFP-10) stimulation in children with a (+) or (−) tuberculin skin test (TST) with in-house tuberculosis contact.Methods We enrolled 40 children aged 1 to 5 years who had an in-house contact with a tuberculous adult. Blood samples were obtained from all children for QuantiFERON tuberculosis (TB) gold in tube (QFT-GIT), and peripheral blood mononuclear blood cell culture tests. The subjects were grouped as TST (−) QFT-GIT (−), TST (+) QFT-GIT (−), and TST (+) QFT-GIT (+). Supernatant of peripheral blood mononuclear cell culture was separated with and without stimulation of ESAT-6 and CFP-10, and IL-18 and IL-27 levels were measured with enzyme linked immunoassay (ELISA) test.Results The study group included 22 boys and 18 girls with mean age 4.25 ± 0.9 years. IL-18 and IL-27 levels were statistically significant in ESAT-6/CFP-10-stimulated supernatants of peripheral blood mononuclear cell (PBMC) samples among the three groups (p = 0.000, p = 0.007, respectively). IL-18 levels between the TST (−) QFT-GIT (−) and TST (+) QFT-GIT (+) groups were significantly different (p = 0.026). Both IL-18 and IL-27 levels were significantly different between ESAT-6/CFP-10 stimulated PBMC supernatants of TST (−) QFT-GIT (−) and TST (+) QFT-GIT (−) groups (p = 0.000, p = 0.003, respectively).Conclusion Low IL-18 and IL-27 responses of peripheral blood mononuclear cells in children with Bacillus Calmette–Guérin (BCG) vaccine may play a role in Mycobacterium tuberculosis infection after in-house contact.
Keywords: childhood tuberculosis; INF-γ release tests; cytokine